Novel Experimental Drugs for Treatment of Multiple Myeloma - Offidani M; Corvatta L; Morè S; Olivieri A (Dove Medical Press, 2021)
Massimo Offidani,1 Laura Corvatta,2 Sonia Morè,1 Attilio Olivieri1 1Clinica di Ematologia Azienda Ospedaliero-Universitaria Ospedali Riuniti di Ancona, Ancona, Italy; 2U.O.C. Medicina, Ospedale Profili, Fabriano, ItalyCorrespondence: Massimo Offidani Email massimo.offidani@ospedaliriuniti.marche.itAbstract: Multiple myeloma (MM) is the second most frequent hematological malignancy characterized by bone marrow aberrant plasma cells proliferation leading to a genetic complex and heterogeneous disease, with a median survival ranging from two to more than 10 years. By using new drugs such as proteasome inhibitors (PIs), immunomodulatory drugs (IMiDs), monoclonal antibodies (mAbs) in different combinations and high-dose therapy followed by auto-transplantation, there has been an amazing improvement in the outcome of this disease in recent years. Despite this, MM is still considered an incurable disease, characterized by remission periods alternated with relapse/progression episodes finally leading to resistant disease. In particular, patients who become refractory to PIs, IMiDs and mAbs have a very poor outcome. Moreover, to overcome resistant residual disease, a large combination of drugs will be increasingly used in early lines of therapy; this further reduces the therapeutic options at each relapse. This natural history means that MM always needs new drugs/strategies to overcome the incoming resistance. New combinations of naked mAbs are becoming the therapy of choice for patients refractory to lenalidomide and/or PI; conjugated mAbs will be useful in triple- and more-refractory patients; CAR-T cells and bispecific mAbs have shown relevant results in very advanced stages of disease. In this review, we reported the results of these new therapies and explored their potential applications. Personalized and precision medicine seem to be the new frontier of cancer treatment. Although no single or few factors have been identified as disease drivers in MM, recurrent gene mutations were recognized and specific compounds targeting these alterations were developed and studied. Therefore, we reviewed these targeted drugs to try to understand what the best therapeutic strategy in MM is.Keywords: multiple myeloma, immunotherapy, CAR T cell therapy, monoclonal antibodies, targeted therapy